2013
DOI: 10.2310/7750.2013.12097
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunologic Characterization in 26 Indian Pemphigus Patients

Abstract: Background: Pemphigus shows geographically variable characteristics.Objective: To study the clinical and immunologic characteristics of Indian pemphigus patients before and after treatment. Methods: Twenty-six Indian pemphigus patients were analyzed with regard to age, gender, clinical features, treatments and response, the results of histopathology, direct and indirect immunofluorescence (IF), enzyme-linked immunosorbent assay (ELISA), and immunoblot analyses.Results: There were 22 pemphigus vulgaris (PV) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Antibodies directed against the 190‐kDa periplakin were found in two patients. Similar findings were found in our previous study on Indian pemphigus patients . None of these patients showed antibodies to both periplakin and envoplakin, the hallmark of paraneoplastic pemphigus.…”
Section: Demographic Data Clinical Features and Immunofluorescence supporting
confidence: 91%
“…Antibodies directed against the 190‐kDa periplakin were found in two patients. Similar findings were found in our previous study on Indian pemphigus patients . None of these patients showed antibodies to both periplakin and envoplakin, the hallmark of paraneoplastic pemphigus.…”
Section: Demographic Data Clinical Features and Immunofluorescence supporting
confidence: 91%
“…Similar findings were found in our previous study on Indian pemphigus patients. 6 None of these patients showed antibodies to both periplakin and envoplakin, the hallmark of paraneoplastic pemphigus.…”
Section: Editormentioning
confidence: 91%
“…All sera were kept at −80 °C for long durations and at 4 °C with 0·1% sodium azide as a preservative during experiments. Studies of the considerably large number of patients used in this study have previously been reported . All previously reported studies for smaller numbers of patients used in this study are listed in Appendix S2 (see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%